2019
DOI: 10.1017/s0022029919000530
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mastitis and the B-mode, colour Doppler ultrasonography measurements of supramammary lymph nodes in cows

Abstract: This research communication aims to test the hypothesis that B-Mode, colour Doppler ultrasonographic measurements and characteristics can identify mastitis in dairy cows. A total of 102 lactating cows were divided into 3 groups: cows in which all mammary quarters were CMT-negative, cows with CMT-positive mammary quarters and cows with clinical mastitis in at least one quarter. Colour Doppler ultrasonography measurements of the supramammary lymph nodes revealed that distortion-type vascular morphology, the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…B-mode ultrasonography was also used to determine the disturbance in milk secretion and the structural changes in the teat cistern and udder tissue [ 115 ]. For the first time in mastitis, Risvanli et al [ 116 ] evaluated the supramammary lymph nodes of cattle by color Doppler ultrasonography because mastitis causes lymphocytic proliferation that leads to morphological changes in the supramammary lymph nodes [ 117 ].…”
Section: Mastitis Diagnosismentioning
confidence: 99%
“…B-mode ultrasonography was also used to determine the disturbance in milk secretion and the structural changes in the teat cistern and udder tissue [ 115 ]. For the first time in mastitis, Risvanli et al [ 116 ] evaluated the supramammary lymph nodes of cattle by color Doppler ultrasonography because mastitis causes lymphocytic proliferation that leads to morphological changes in the supramammary lymph nodes [ 117 ].…”
Section: Mastitis Diagnosismentioning
confidence: 99%
“…A minimum of three continuous and consecutive waves are needed for an accurate evaluation. The parametres measured in most studies are the following: (a) peak systolic velocity (PSV), (b) end diastolic velocity (EDV), (c) resistance index [RI = (PSV − EDV)/PSV], and (d) pulsatility index [PI = (PSV − EDV)/TAMV] (TAMV: time-averaged maximum velocity); in some cases, important information can also be extracted by (e) systolic: diastolic velocity ratio [SV/DV = (ASF/ADF)] (ASF: average diastolic flow and ADF: average systolic flow), (f) time-averaged maximum velocity (TAMV), (g) systolic acceleration (A), and (h) total blood volume [Q = (TAV mea n × S)] (TAV mean : time-averaged mean velocity, S: cross-sectional surface of the vessel) [ 41 , 42 ]. Finally, the characterization of blood flow pattern has also been reported, as the laminar or turbulent flow and the high or low resistivity are observations that may contribute to the diagnosis [ 43 ].…”
Section: Ultrasonographymentioning
confidence: 99%
“…Santos et al [ 55 ] have indicated that increased PSV and RI in cases of mastitis in goats are probably related to more severe infections. Furthermore, the examination of the supramammary lymph nodes may also provide useful information regarding infection in cows [ 42 ].…”
Section: Ultrasonographymentioning
confidence: 99%
“…This was performed as described by Risvanli et al (2019). Measurements were made accordingly regarding the vascular distribution category, vascular density and the vascular morphological appearance in the portio vaginalis of the cervix.…”
Section: Colour Doppler Ultrasonography Measurementmentioning
confidence: 99%